Social capital and community disaster resilience in a disaster-prone area in Indonesia - Johan Budhiana; Rosliana Dewi; Iwan Permana; Nurvita Trianasari; Waqid Sanjaya; Abdul Rahman La Ede; Dedi Wahyudin (Faculty of Nursing Universitas Padjadjaran, 2026)
Introduction: Communities in disaster-prone areas face repeated exposure to natural hazards, yet the role of social capital in enhancing disaster resilience is underexplored in Indonesia. Objective: This study aimed to examine the relationship between dimensions of social capital—social cohesion, social participation, and reciprocity—and community disaster resilience in Sukabumi, West Java. Methods: A cross-sectional survey was conducted among 700 residents aged ≥18 years using an online questionnaire. Disaster resilience was measured with the Brief Resilience Scale, and social capital with validated subscales. Multiple linear regression analyzed associations between social capital and resilience. Results: Older age, higher education, experience of housing damage (22.4%), loss of friends or relatives (44.6%), and higher levels of social cohesion, participation, and reciprocity were significantly associated with greater disaster resilience (all p<0.05). The regression model explained 56% of the variance (R²=0.56). Conclusion: Social capital is a significant predictor of community disaster resilience in high-risk areas. These findings can guide health professionals, especially nurses, to design targeted interventions for disaster preparedness and long-term recovery.